Surface-protective film with release film

KR103019186B1Active Publication Date: 2026-09-11ZACROS CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020240042585
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-03-31
Filing Date
2024-03-28
Publication Date
2026-09-11
Estimated Expiration
2044-03-28

Smart Images

  • Figure 112024034957110-PAT00007_ABST
    Figure 112024034957110-PAT00007_ABST
Patent Text Reader

Abstract

A surface protection film is provided that has a release film formed using a non-silicon-based release layer, which is resistant to zipping. As a surface protection film (10) having a release film formed thereon, the surface protection film (16) has a first substrate layer (14) made of a polyethylene terephthalate film and an adhesive layer (13) made by crosslinking a (meth)acrylate copolymer, and the surface protection film (16) is a surface protection film for optical or electronic use, and the release film (15) has a second substrate layer (11) and a release layer (12) formed on one side of the second substrate layer (11), the release layer (12) of the release film (15) includes an amino structure, and the Si in the release layer (12) of the release film (15) is 0.5 kcps or less as a fluorescent X-ray.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a surface protection film having a release film formed thereon. Background Technology

[0002] Surface protection films are used to protect the surfaces of optical components, electronic components, etc.

[0003] For example, Patent Document 1 describes an optical surface protection film having a separator formed on a surface opposite to a polyester film of an adhesive layer, wherein the intensity of Si-Kα rays in fluorescent X-rays on the surface of the adhesive layer after peeling off the separator is 2.5 kcps or less. Additionally, Patent Document 2 describes an optical surface protection film having a separator formed thereon, wherein the separator is a substrate and a non-silicon release layer is formed thereon. Prior art literature

[0004] Japanese Published Patent Application No. 2016-145341 Japanese Published Patent Application No. 2017-31278 The problem to be solved

[0005] When using a non-silicone release layer, zipping is prone to occur when peeling the release film from the adhesive layer of the surface protection film. Here, zipping refers to the phenomenon where the release film cannot be peeled from the adhesive layer of the surface protection film with a constant force, resulting in minute vibrations during peeling that leave peeling marks on the adhesive layer or produce a peeling sound.

[0006] The present invention aims to provide a surface protection film having a release film formed thereon that is resistant to zipping. means of solving the problem

[0007] A first embodiment of the present invention is a surface protection film having a release film formed thereon, wherein the surface protection film has a first substrate layer made of a polyethylene terephthalate film and an adhesive layer formed by crosslinking a (meth)acrylate copolymer, and the surface protection film is a surface protection film for optical or electronic use, and the release film has a second substrate layer and a release layer formed on one side of the second substrate layer, wherein the release layer of the release film includes an amino structure, and the Si in the release layer of the release film is 0.5 kcps or less as a fluorescent X-ray.

[0008] A second embodiment is a surface protection film formed with a release film, wherein, in the first embodiment, the surface protection film has a Tg of +22°C or lower, and the release layer of the release film contains a component that does not chemically react with the amino structure.

[0009] A third embodiment is a surface protection film having a release film formed thereon, wherein, in the first or second embodiment, the Tg of the surface protection film is +11℃ or lower.

[0010] The fourth embodiment is a surface protection film having a release film formed thereon, wherein in any one of the first to third embodiments, when the release film is peeled at a peeling speed of 0.3 m / min and a peeling angle of 180 degrees, the instantaneous maximum value of the peeling force is B, and when the release film is peeled at a peeling speed of 0.3 m / min and a peeling angle of 180 degrees, the average peeling force is C, and the value A obtained by the formula: A = B / C is 1.5 or less.

[0011] The fifth embodiment is a surface protection film having a peel film formed thereon, wherein, in any one of the first to fourth embodiments, when the peel film is peeled at a peeling speed of 0.3 m / min and a peeling angle of 180 degrees, the average peeling force is C, and C is greater than 0.02 N / 25 mm.

[0012] The sixth embodiment is a surface protection film in which, in any one of the first to fifth embodiments, a release film is formed in which the release layer of the release film comprises a melamine structure.

[0013] The seventh embodiment is a surface protection film in which, in any one of the first to sixth embodiments, a release film is formed on the release layer comprising any one of acrylic, polyol, and polyether. Effects of the invention

[0014] According to the present invention, a surface protection film formed with a release film using a non-silicone release layer that is resistant to zipping can be provided. Brief explanation of the drawing

[0015] Figure 1 is a cross-sectional view showing an example of a surface protection film having a release film formed thereon. Specific details for implementing the invention

[0016] The present invention will be described below based on preferred embodiments.

[0017] As shown in FIG. 1, the surface protection film (10) formed with a release film of the embodiment has a release film (15) and a surface protection film (16).

[0018] The surface protection film (16) has a first substrate layer (14) made of a polyethylene terephthalate (PET) film and an adhesive layer (13) made by crosslinking a (meth)acrylate copolymer. The surface protection film (16) is a surface protection film for optical or electronic use.

[0019] The peeling film (15) has a second substrate layer (11) and a peeling layer (12) formed on one side of the second substrate layer (11). The peeling layer (12) of the peeling film (15) includes an amino structure. The Si in the peeling layer (12) of the peeling film (15) is 0.5 kcps or less as a fluorescent X-ray.

[0020] In the surface protection film (10) on which the peeling film of the embodiment is formed, the Si in the peeling layer (12) of the peeling film (15) is 0.5 kcps or less as a fluorescent X-ray. The amount of Si in the peeling layer (12) can be quantified by the intensity (kcps) of the Si-Kα rays using fluorescent X-ray analysis. The amount of Si in the peeling layer (12) is a value that does not include the amount of Si in the second substrate layer (11). The amount of Si in the peeling layer (12) may be obtained by measuring the amount of Si in the peeling film (15) from the peeling layer (12) side and then subtracting the amount of Si in the second substrate layer (11) that does not have the peeling layer (12).

[0021] By having a small amount of Si in the peeling layer (12), it can be confirmed that the content of silicon-based components, such as organic silicon compounds, in the peeling layer (12) is small. If the peeling layer contains silicon-based components, there is a risk that the silicon-based components will migrate in large quantities to the surface of the adhesive layer when the peeling film and the surface protection film are laminated. In addition, there is a risk that the silicon-based components migrated to the surface of the adhesive layer may contaminate the surface of the substrate, such as an optical component or an electronic component. Therefore, by keeping the amount of Si in the peeling layer (12) within the range described above, surface contamination of the adhesive layer or the substrate can be suppressed.

[0022] In the surface protection film (10) having a release film formed according to the embodiment, the release film (15) includes an amino structure in the release layer (12). The release layer (12) including the amino structure may include a component having an amino structure. Specific examples include a composition consisting of one component having an amino structure, a composition consisting of two or more components having an amino structure, and a composition consisting of at least one component having an amino structure and at least one component not having an amino structure.

[0023] The peeling layer (12) may be composed of one component or two or more components. If the peeling layer (12) is composed of a composition containing two or more components, chemical reactions, chemical bonding, etc. may occur between the components included in the composition.

[0024] The component having an amino structure is not particularly limited, but the peeling agent component included in the peeling layer (12) may be a component having an amino structure. The component having an amino structure is preferably a component that does not have Si, such as a silicon-based peeling agent. The component other than the silicon-based peeling agent may be a component other than a long-chain alkyl material. The peeling layer (12) may include a component having an amino structure without having a long-chain alkyl, and a component having a long-chain alkyl without having an amino structure. The peeling agent component in the peeling layer (12) may be one type or two or more types.

[0025] Specific examples of components having an amino structure include amino resins such as melamine resin and aminoalkyd resin. The aminoalkyd resin may include a mixture of amino resin and alkyd resin. The amino structure included in the peeling layer (12) may be a melamine structure or an amino structure other than a melamine structure.

[0026] Amino resin is a resin produced by the condensation of a compound having an amino group, such as melamine, urea, benzoguanamine, and aniline, and a compound having an aldehyde group, such as formaldehyde. Amino resin can be used as a thermosetting resin, either alone or in combination with alkyd resin, acrylic resin, epoxy resin, etc.

[0027] It is preferable that the release film (15) includes a melamine structure in the release layer (12). The release layer (12) including the melamine structure may include a component having a melamine structure. Specific examples include a composition consisting of one component having a melamine structure, a composition consisting of two or more components having a melamine structure, and a composition consisting of at least one component having a melamine structure and at least one component not having a melamine structure.

[0028] The component having a melamine structure is not particularly limited, but the peeling agent component included in the peeling layer (12) may be a component having a melamine structure. Specific examples of components having a melamine structure include melamine resin.

[0029] Examples of melamine resins include alkylated melamine resins such as methylated melamine resin, ethylated melamine resin, and butylated melamine resin. More specifically, examples include full ether-type methylated melamine resin and methylol-type methylated melamine resin.

[0030] The thickness of the peeling layer (12), additives, etc., can be appropriately designed. The peeling layer (12) may include any of the following components other than the component having an amino structure: a component that chemically reacts with the amino structure, a component that does not chemically react with the amino structure, or other components.

[0031] A component that does not chemically react with an amino structure may be a transfer component capable of transferring from the release layer (12) to the adhesive layer (13). The transfer component may be added in a small amount compared to the release agent component. For example, the total amount of the release layer (12) may be 100 parts by weight, and the release agent component may be mixed in the range of 60 to 99 parts by weight and the transfer component in the range of 1 to 40 parts by weight. The transfer component in the release layer (12) may be one type or two or more types.

[0032] The amount of the above-mentioned transfer component is not particularly limited, but with the total amount of the peeling layer (12) being 100 parts by weight, it may be 39 parts by weight or less. The transfer component may be 35 parts by weight or less, 30 parts by weight or less, 25 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, or less.

[0033] If the peeling layer (12) contains components other than the peeling agent component and the transfer component, the total amount of the peeling layer (12) is 100 parts by weight, and the components other than the peeling agent component and the transfer component may be 39 parts by weight or less. The amount of components other than the peeling agent component and the transfer component is not particularly limited, but may be 35 parts by weight or less, 30 parts by weight or less, 25 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, or less than that.

[0034] It is preferable that the peeling layer (12) includes any one of acrylic, polyol, and polyether. More specifically, it is preferable that the peeling layer (12) includes at least one of acrylic, polyol, and polyether as a component. Any one of acrylic, polyol, or polyether may be a component that does not have an amino structure, may be a transition component as described above, may be a component that chemically reacts with an amino structure, or may be a component that does not chemically react with an amino structure.

[0035] A release film (15) containing the above-mentioned transfer component in the release layer (12) is preferably of a non-transfer type in which the transfer to the adhesive layer is minimal. Additionally, a release film (15) that does not contain the transfer component in the release layer (12) is of a non-transfer type in which there is no transfer to the adhesive layer.

[0036] Even if it is a non-transfer type or a non-transfer type, the occurrence of zippering can be suppressed. A non-transfer type release film (15) is more preferable because it can suppress the occurrence of zippering even when combined with a surface protection film (16) having an adhesive layer (13) that is relatively hard and has a high Tg compared to a non-transfer type release film (15).

[0037] The above acrylic may be any component having an acrylic structure, and examples include acrylic compounds, acrylic polymers, acrylic resins, etc.

[0038] The above polyol can be any component having a polyol structure, and for example, a polyol compound may be used.

[0039] The above polyether may be any component having a polyether structure, and examples include polyether compounds.

[0040] The peeling layer (12) may include a polyol compound having a polyether structure, such as polyethylene glycol or polypropylene glycol.

[0041] If necessary, additives may be added to the peeling layer (12). Examples of additives include stabilizers, antioxidants, ultraviolet absorbers, antistatic agents, thickeners, lubricants, foaming agents, defoaming agents, inorganic particles, organic particles, etc. Additionally, the peeling layer (12) may be formed without containing these additives. As for the lubricant, fatty acid esters may be used, although they are not particularly limited.

[0042] As an additive to the peeling layer (12), a sulfonic acid such as p-toluenesulfonic acid may be used. The sulfonic acid may also serve as a catalyst for the curing reaction of the melamine resin. When curing the melamine resin, if necessary, the coating film applied on the second substrate layer (11) may be treated under heating conditions.

[0043] Since the amino resin (a component having an amino structure), such as melamine resin, included in the peeling layer (12) is cured, the transfer from the peeling layer (12) to the adhesive layer (13) is suppressed. In addition, the component that chemically reacts with the amino structure also becomes bonded with the cured resin, so the transfer to the adhesive layer (13) is suppressed. For this reason, it is preferred for a non-transfer type or non-transfer type peeling layer (12).

[0044] As for the second substrate layer (11) of the release film (15), a polyester resin film such as a polyethylene terephthalate (PET) film may be used, although it is not particularly limited. The thickness and additives of the second substrate layer (11) can be appropriately designed. The second substrate layer (11) may include silicon (Si) compounds such as silica (SiO2), silicates, clay minerals, and zeolites as anti-blocking agents or fillers.

[0045] The surface protection film (16) of the illustrated example has an adhesive layer (13) on one side of the first substrate layer (14). The adhesive layer (13) is formed by crosslinking a (meth)acrylate-based copolymer. Examples of (meth)acrylate-based copolymers include copolymers of two or more monomers, such as (meth)acrylic acid monomers or (meth)acrylic acid derivative monomers such as (meth)acrylate and (meth)acrylamide. The thickness and additives of the adhesive layer (13) can be appropriately designed.

[0046] In this specification, (meth)acrylate means acrylate and / or methacrylate. (Meta)acrylic acid, (meth)acrylate, (meth)acrylamide, etc. likewise means acrylic acid and / or methacrylic acid or derivatives thereof.

[0047] To crosslink (meth)acrylate copolymers, UV curing, electron beam curing, crosslinking agents, etc. may be used. The crosslinking agent may be a radical crosslinking agent such as peroxide, or a reactive crosslinking agent such as isocyanate compounds or epoxy compounds.

[0048] A reactive crosslinking agent can crosslink the copolymer by reacting with polar functional groups, such as hydroxyl or carboxyl groups, contained in the (meth)acrylate copolymer. A (meth)acrylate copolymer having polar functional groups can be obtained by copolymerizing a (meth)acrylate monomer having polar functional groups with a (meth)acrylate copolymer.

[0049] The Tg of the surface protection film (16) is preferably +22°C or lower, and more preferably +11°C or lower. The Tg of the surface protection film (16) can be measured by mounting the surface protection film (16), which has a first substrate layer (14) and an adhesive layer (13), onto a viscoelasticity measuring device.

[0050] Tg generally refers to the glass transition temperature. The glass transition temperature (Tg) is a type of transition temperature and can be measured using various methods such as differential scanning calorimetry (DSC), differential thermal analysis (DTA), and dynamic viscoelasticity measurement (DMA).

[0051] When measuring the temperature dependence of the loss tangent tan δ using dynamic viscoelasticity measurement, the glass transition temperature (Tg) is detected from the peak temperature rather than from inflection points or baseline shifts, making measurement easier. For this reason, even in the case of a laminate of heterogeneous materials such as a surface protection film (16), the apparent Tg of the surface protection film (16) can be obtained by observing the apparent peak.

[0052] The Tg of the surface protection film (16) is not limited to meaning that the adhesive layer (13) and the first substrate layer (14) undergo glass transition at the same temperature, and it is sufficient if the value of Tg can be measured by the method described above. The glass transition temperature (Tg) of the polyethylene terephthalate film constituting the first substrate layer (14) and the glass transition temperature (Tg) of the crosslinked (meth)acrylate copolymer constituting the adhesive layer (13) do not necessarily have to match.

[0053] In the design of acrylic adhesives, it is common practice to control the glass transition temperature (Tg) of the (meth)acrylate copolymer prior to crosslinking. The glass transition temperature (Tg) of the (meth)acrylate copolymer is not particularly limited, but to obtain a flexible adhesive layer (13), for example, it is preferable to be less than -30°C, and additionally, it may be between -70°C and -40°C.

[0054] According to the surface protection film (10) formed with the release film of the embodiment, since the range of selectable Tg is wide, the (meth)acrylate copolymer used in the adhesive layer (13) may be selected with a relatively low Tg that is the same as conventional, or a high Tg that is higher than conventional. Depending on the application or performance of the surface protection film (16), the (meth)acrylate copolymer can be appropriately designed.

[0055] Polyethylene terephthalate (PET) film is used as the first substrate layer (14) of the surface protection film (16). The thickness and additives of the first substrate layer (14) can be appropriately designed. The first substrate layer (14) may include silicon (Si) compounds such as silica (SiO2), silicates, clay minerals, and zeolites as anti-blocking agents or fillers.

[0056] In the present specification, the instantaneous maximum value of the peeling force (instantaneous maximum peeling force) when the peeling film (15) is peeled at a peeling speed of 0.3 m / min and a peeling angle of 180 degrees is denoted as B, and the average peeling force when the peeling film (15) is peeled at a peeling speed of 0.3 m / min and a peeling angle of 180 degrees is denoted as C. These peeling forces are measured by peeling the peeling film (15) from the adhesive layer (13) of the surface protection film (16).

[0057] Formula: When the value of the ratio obtained by A = B / C is set to A, it is preferable that the value of A be 1.5 or less, and more preferable that it be 1.2 or less. When the value of the ratio A of instantaneous maximum peel force / average peel force is small, it is difficult for zipping to occur when peeling the peel film (15) from the surface protection film (16).

[0058] It is preferable that the value of the average peel force C be greater than 0.02 N / 25 mm, and more preferable that it be greater than 0.04 N / 25 mm. If the value of the average peel force C is small, it is easy to peel the peel film (15) from the surface protection film (16).

[0059] In a surface protection film (10) having a release film formed thereon, a release film (15) is superimposed on a surface protection film (16) with the release layer (12) facing the adhesive layer (13). The surface protection film (16) is used to protect the surface of a protected object in a state where the release film (15) is peeled off from the surface protection film (10) having a release film formed thereon. At this time, the adhesive layer (13) is used to bond the surface protection film (16) to the surface of the protected object.

[0060] The objects to be protected by the surface protection film (16) are not particularly limited to optical components or electronic components, but may include optical films, optical glass, polarizers, phase difference plates, display panels, touch panels, etc. Examples of optical films include polarizing films, phase difference films, anti-reflective films, anti-glare films, ultraviolet absorption films, infrared absorption films, optical compensation films, brightness enhancement films, etc.

[0061] It is preferable that the surface protection film (16) be colorless and transparent so that the condition of the object to be protected can be visually checked even when the surface protection film (16) is laminated. The release film (15) may also be colorless and transparent. It is possible to select a colorless and transparent material as the second substrate layer (11), the release layer (12), the adhesive layer (13), and the first substrate layer (14).

[0062] The surface protection film (16) may be used only during the manufacturing process of the object to be protected, or it may remain laminated to the object to be protected even after shipment. In order for the surface protection film (16) to continue protecting the surface of the object to be protected, it is desirable for the surface protection film (16) to have a suitable adhesive force on the object to be protected. When peeling the surface protection film (16) from the object to be protected, it is desirable that the adhesive force of the surface protection film (16) on the object to be protected is not excessively high.

[0063] Although the present invention has been described above based on preferred embodiments, the present invention is not limited to the embodiments described above, and various modifications are possible within the scope of not departing from the essence of the present invention.

[0064] Examples

[0065] The present invention will be specifically explained below through examples.

[0066] <Method for Manufacturing Release Film>

[0067] Four types of release films were produced by applying the following paint for forming a release layer onto a PET film with a thickness of 38 μm (manufactured by Mitsubishi Chemical Co., Ltd., Diafoil (registered trademark) T100) and drying it. "Part" refers to a part by weight.

[0068] In release film 1 (hereinafter referred to as “RF-1”), a paint was used in which 3 parts of the curing agent “Aracoat (registered trademark) RA2000” manufactured by Arakawa Kagaku High School Co., Ltd. were added to 100 parts of the main ingredient “Aracoat (registered trademark) RL900” manufactured by Arakawa Kagaku High School Co., Ltd.

[0069] The paint used in RF-1 includes a component having an amino structure (melamine), a component that chemically reacts with the amino structure (polyol), and a component that does not chemically react with the amino structure (acrylic). Among these, the component that contributes to peelability is acrylic.

[0070] In the release film 2 (hereinafter referred to as “RF-2”), a paint was used in which 10 parts of polypropylene glycol (weight average molecular weight 1000) and 3 parts of p-toluenesulfonic acid were added to 90 parts of full ether-type methylated melamine resin “Simel (registered trademark) 303LF” manufactured by Allnex.

[0071] The paint used on RF-2 contains a component having an amino structure (melamine), a component that does not chemically react with the amino structure (polypropylene glycol), and other components (paratoluenesulfonic acid). Among these, the component that contributes to peelability is polypropylene glycol.

[0072] In release film 3 (hereinafter referred to as “RF-3”), a paint was used in which 30 parts of an acrylic polymer (manufactured by Fujimori High School Co., Ltd., hydroxyl value 59.8 mgKOH / g) and 3 parts of p-toluenesulfonic acid were added to 70 parts of Allnex-manufactured methylol-type methylated melamine resin “Simel (registered trademark) 370”.

[0073] The paint used in RF-3 contains a component having an amino structure (melamine), a component that chemically reacts with the amino structure (acrylic polymer), and other components (paratoluenesulfonic acid). Among these, the component that contributes to peelability is the acrylic polymer.

[0074] In the release film 4 (hereinafter referred to as “RF-4”), a paint was used in which 3 parts of a p-toluenesulfonic acid solution “Dryer 900” manufactured by Resonac Co., Ltd. were added to 100 parts of a long-chain alkyl-modified aminoalkyd resin “Tespain (registered trademark) 303” manufactured by Resonac Co., Ltd.

[0075] The paint used in RF-4 contains a component having an amino structure, a component that chemically reacts with the amino structure (alkyd), and other components (paratoluenesulfonic acid). Among these, the component that contributes to peelability is the alkyd.

[0076] Additionally, as a release film 5 (hereinafter referred to as “RF-5”), a release film “Diafoil (registered trademark) MRF” manufactured by Mitsubishi Chemical Co., Ltd. (substrate thickness: 38㎛) was used.

[0077] Among RF-1 to RF-4, RF-1 and RF-2 are non-transferring types, and their "components that do not chemically react with the amino structure" are transferring components. RF-3 and RF-4 are non-transferring types that do not use transferring components. RF-5 is a type in which components such as silicone are transferred in large quantities from the release layer to the adhesive layer.

[0078] <Preparation of (Meta)Acrylate-Based Copolymers>

[0079] Nitrogen gas was introduced into a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube to replace the air inside the reaction apparatus with nitrogen gas. Subsequently, 90 parts by weight of the monomers shown in (A) to (C) of Table 1 and a solvent (ethyl acetate) were added to the reaction apparatus. Then, 0.1 parts by weight of dimethylazobisisobutyrate was added dropwise over 2 hours as a polymerization initiator, and the reaction was carried out at 65°C for 6 hours to obtain a (meth)acrylate copolymer.

[0080] The five types of (meth)acrylate copolymers obtained are hereinafter referred to as “AP-A”, “AP-B”, “AP-C”, “AP-D”, and “AP-E”, respectively. Meanwhile, although the measurement results are not specifically shown, the weight average molecular weight of the obtained (meth)acrylate copolymers is within the range of 100,000 to 1,000,000.

[0081] The monomers used are 2-ethylhexyl acrylate (2EHA), dimethylacrylamide (DMAA), and 4-hydroxybutyl acrylate (4HBA), respectively. The values ​​in parentheses in (A) to (C) of Table 1 represent the weight parts of each monomer.

[0082]

[0083] <Calculation of Tg of (Meta)Acrylate Copolymers>

[0084] The Tg (°C) of the (meth)acrylate copolymer was calculated using the following formula from the glass transition temperature Tgn (°C) of the homopolymer for each monomer and the weight fraction Wn of each monomer.

[0085] 1 / (Tg+273)=Σ[Wn / (Tgn+273)]

[0086] The Tgn of the homopolymers was set from literature values ​​to -70°C for 2EHA, +119°C for DMAA, and -32°C for 4HBA. Σ represents the sum of the values ​​of the term [Wn / (Tgn+273)] calculated for each monomer. The results are shown in Table 1 above.

[0087] <Preparation of Adhesive Composition and Surface Protection Film>

[0088] To the (meth)acrylate copolymer shown in (E) of Table 2, the crosslinking agent TKA-100 (isocyanurate of a hexamethylene diisocyanate compound, manufactured by Asahi Kasei Co., Ltd.) shown in (F) of Table 2 was added and stirred to obtain an adhesive composition. The values ​​in parentheses in (E) to (F) of Table 2 represent the weight parts of the (meth)acrylate copolymer and the crosslinking agent, respectively.

[0089] After applying the obtained adhesive composition onto a PET film with a thickness of 38 μm (manufactured by Mitsubishi Chemical Co., Ltd., Diafoil (registered trademark) T100), the solvent was removed by drying at 120°C, and a surface protection film with an adhesive layer thickness of 15 μm was obtained.

[0090] The 10 types of surface protection films obtained are hereinafter referred to as “PF-A1”, “PF-A2”, “PF-B1”, “PF-B2”, “PF-C1”, “PF-C2”, “PF-D1”, “PF-D2”, “PF-E1”, and “PF-E2”, respectively.

[0091]

[0092] <Method for Measuring Tg of Surface Protection Film>

[0093] The surface protection film was mounted on a solid shear jig, which is an option of the viscoelasticity measuring device (product name "Rheogel-E4000", manufactured by UBM Co., Ltd.). The storage modulus and loss modulus were measured in shear mode under conditions of a deformation amount of 1% and a frequency of 1 Hz, while increasing the device's set temperature from -50°C to +100°C at a heating rate of 2°C / min. From the results, the loss tangent tanδ of the surface protection film for every 1°C was calculated. The temperature at which this loss tangent value reaches a maximum was set as the Tg of the surface protection film. The results are shown in Table 2 above.

[0094] In practice, the Tg of the surface protection film was measured by manufacturing a surface protection film with a release film formed thereon using the manufacturing method described below, peeling off the release film, and mounting it on a viscoelasticity measuring device. However, since there is no difference in the Tg of the surface protection film due to differences in the release film, the results were presented for each surface protection film without distinguishing between the types of release films.

[0095] <Method for Measuring the Amount of Si Included in the Exfoliating Layer>

[0096] The amount of Si present on the peeling layer surface of the peeling film was defined as F(kcps) and measured by fluorescence X-ray analysis. The above fluorescence X-ray analysis was performed using an XRF device manufactured by Rigaku Co., Ltd., model "ZSX (registered trademark) PrimsTVi", with a measurement range: within a circle of 30 mm diameter, detection X-ray: Si-Kα, output: 30 kV, 100 mA, and spectroscopic crystal PETH.

[0097] As a blank, the amount of Si present per area corresponding to a circle of 30 mm of the substrate film used in the release film was defined as A(kcps), and measured by fluorescence X-ray analysis under the same conditions as F(kcps). The value obtained by subtracting A(kcps) from F(kcps) was defined as the amount of Si (kcps) contained in the release layer.

[0098]

[0099] <Method for manufacturing a surface protection film with a formed release film and method for measuring release strength>

[0100] One type selected from the 5 types of release films shown in Table 3 was laminated to one type selected from the 10 types of surface protection films shown in Table 2. By doing so, a surface protection film was manufactured with a total of 50 types of release films formed.

[0101] A test specimen was prepared by cutting a surface protection film with a release film formed thereon to a width of 25 mm and a length of 150 mm. The surface protection film side of the test specimen was fixed to a test device, and the peeling force (N / 25 mm) was measured by gripping and peeling the release film. The peeling speed was set to 0.3 m / min and the peeling angle to 180°.

[0102] Using a desktop precision universal testing machine (manufactured by Shimadzu Seisakusho Co., Ltd., Autograph (registered trademark) AGS-X), peeling was performed for a length of 120 mm, and the peel force was measured at a frequency of 60 times per second. From these measurement results, the peel force at which the maximum value was instantaneously reached was set as B, and the average value of the peel force was set as C. Additionally, the value of A = B / C was calculated.

[0103] The results are shown in Table 4 for the measured value of B (instantaneous maximum value), Table 5 for the measured value of C (average value), and Table 6 for the value of A = B / C.

[0104]

[0105]

[0106]

[0107] RF-1 to RF-4 all have a Si amount in the exfoliation layer of 0.5 kcps or less as fluorescent X-ray.

[0108] For RF-1 and RF-2, in each of the 8 types of PF-A1 to PF-D2, the value of A=B / C was reduced, and zipping could be suppressed.

[0109] For RF-3 and RF-4, in each of the six types of PF-A1 to PF-C2, the value of A=B / C was reduced, and zipping could be suppressed.

[0110] In RF-5, the value of A=B / C was small for all 10 types of surface protection films, so zippering could be suppressed, but the release layer contained a lot of Si.

[0111] In the combination of RF-1 or RF-2 and PF-A1 to PF-D2, the Tg of the surface protection film is +22°C or lower, and the release layer of the release film contains a component having an amino structure and a component that does not chemically react with the amino structure. In addition, in the combination of RF-1 to RF-4 and PF-A1 to PF-C2, the Tg of the surface protection film is +11°C or lower, and the release layer of the release film contains an amino structure. Explanation of the symbols

[0112] 10… surface protection film having a release film formed thereon, 11… second substrate layer, 12… release layer, 13… adhesive layer, 14… first substrate layer, 15… release film, 16… surface protection film.

Claims

Claim 1 A surface protection film having a release film formed thereon, wherein the surface protection film has a first substrate layer made of a polyethylene terephthalate film and an adhesive layer formed by crosslinking a (meth)acrylate copolymer, wherein the surface protection film is a surface protection film for optical or electronic use, wherein the release film has a second substrate layer and a release layer formed on one side of the second substrate layer, wherein the release layer of the release film includes an amino structure, wherein the Si in the release layer of the release film has a fluorescent X-ray value of 0.5 kcps or less, wherein B is the instantaneous maximum value of the peeling force when the release film is peeled at a peeling speed of 0.3 m / min and a peeling angle of 180 degrees, and C is the average peeling force when the release film is peeled at a peeling speed of 0.3 m / min and a peeling angle of 180 degrees, and the value A obtained by the formula: A = B / C is 1.5 or less. Claim 2 A surface protection film having a release film formed thereon, wherein the surface protection film has a Tg of +22℃ or lower, and further, the release layer of the release film comprises a component that does not chemically react with the amino structure. Claim 3 A surface protection film having a release film formed thereon, wherein the Tg of the surface protection film is +11℃ or lower in claim 1. Claim 4 delete Claim 5 A surface protection film having a release film formed thereon, wherein, in claim 2 or 3, when the release film is peeled at a peeling speed of 0.3 m / min and a peeling angle of 180 degrees, the average peeling force is C, and C is greater than 0.02 N / 25 mm. Claim 6 A surface protection film having a release film formed thereon, wherein the release layer of the release film comprises a melamine structure, in accordance with claim 2 or 3. Claim 7 A surface protection film having a release film formed thereon, wherein the release layer comprises any one of acrylic, polyol, or polyether, in accordance with claim 2 or 3.

Citation Information

Patent Citations

  • Release film and process for producing the film

    KR1020070079299A

  • Surface-protective film and optical component attached with the same

    KR1020220123626A

  • Optical surface protective film with separator

    KR1020170108004A

  • Peeling sheet

    KR1020210145132A